Forschung in der digitalen Welt. Sicherung, Erschließung und Aufbereitung von Wissensbeständen - Hering, Rainer; Sarnowsky, Jürgen; Schäfer, Christoph; Schäfer, Udo; der Freien und Hansestadt Hamburg, Staatsarchiv (Veröffentlichungen aus dem Staatsarchiv der Freien und Hansestadt Hamburg, 2006)
Today, digitization projects in the Humanities require the implementation of larger, supraregional solutions. The contributions in this volume were presented at the conference of the Hamburg State Archives and the Center for the Humanities in the Digital World at the University of Hamburg on April 10 and 11, 2006. They make an interdisciplinary contribution to the required standardisation of corresponding services which can only facilitate the urgently needed exchange of information and make it possible to share structured data.